A review of transport organisations for female professionals and their impacts on the transport sector workforce. (June 2019) - Fraszczyk, Anna; Piip, Janene
Abstract: The paper offers a review of various national and international organisations established to unite female transport professionals and to enhance their careers in the male-dominated rail environment. The organisations, representing both mode-specific (e.g. Women in Rail in the rail sector in the United Kingdom) as well as general transport and mobility groups (e.g. Women in Logistics & Transport at Chartered Institute of Logistics and Transport, international), are compared in terms of their: size, coverage and type of activities delivered (including mentoring, networking and other). In addition, female rail transport professionals participated in the research to better understand the challenges and opportunities faced at work, and the role of professional organisations, if any, in their careers. Finally, based on the analysis of data, recommendations are addressed to the rail sector's organisations as well as current and potential employees (male and female).